Factors Affecting Nursing Ability To Know Acute Coroner Syndrome In Emergency Installation - Riyadi, Agus; Karmiati, Karmiati (Journal Of Nursing Practice, 2018)
Background: Coronary heart disease is the most cardiovascular disease that causes death in the world. The ability of nurses to recognize acute coronary syndromes is very necessary as part of the emergency services team. Purpose : The purpose of this study was to determine the description of the factors that influence the ability of nurses to know acute coronary syndrome in the emergency department of dr. Iskak Tulungagung. Methods : The design of this research is descriptive analytic with a cross sectional approach with the population of all nurses who work in the Emergency Department of dr. Iskak Tulungagung. The population is 55 nurses. The sample is all of the population, namely 55 respondents with total sampling sampling techniques. The data that has been collected is processed by a statistical test of Multivariate Analysis, Ordinal Regression with significance ? = 0.05. Result : The results showed that most of the respondents with D3 education were 33 respondents (60.0%), almost all respondents had never attended ECG training in the amount of 50 respondents (90.9%) and almost half of the respondents had a working period of 2-5 year is 25 respondents (45.5%). The results of the regression regression analysis showed that the p-value = 0.855 on the education factor which means that H0 was accepted, the p-value = 0.041 in the training factor which means H1 is received, the p-value = 0.003 on the working period, which means that H1 is accepted Conclusion : Based on research, education does not affect the ability to recognize acute coronary syndrome. The education obtained will develop according to the increase in the work period and the frequent training that is obtained and practiced directly in real situations